Equating Method for Prevent Discrimination in Classroom - Deni Iriyadi; Dali Santun Naga; Wardani Rahayu (Journal of Educational Science and Technology (EST), 2019)
This study aims to determine effectivenes Simplified Cirlce Arc method used at the school level to prevent discrimination against student grades. This study National Examination data on mathematics subjects from of the Center for Educational Assessment in DKI Jakarta and Tangerang regions. Using the Rasch Model analysis, data obtained for 2135 in the DKI Jakarta (X) and 2271 in the Tangerang area (Y). The data was obtained after conducting Rasch analysis with Mean Square Outfit (MNSQ) of 0.5 <MNSQ <1.5. Replication is done 50 times for each form data distribution from each region. Results of replication then RMSE value is calculated. The results showed that equal form with normal data distribution, statistically the average RMSE with the Simplified Circle Arc method smaller than the average RMSE result of equalization with the Nominal Weight Mean method which indicates that the Simplified Circle Arc method more accurate than Nominal Weight Mean method. Likewise, with equal equations with positive skeweness and negative skewness data distribution, the average RMSE with the Simplified Circle Arc Method is smaller than average RMSE resulting in equalization of the score with Nominal Weight Mean method. A small RMSE value indicates a fairly accurate result of equalization.